Особенности электроразрядной обработки смесей на основе порошков Fe и Ti различного состава - Сизоненко, О.Н.; Тафтай, Э.И.; Присташ, Н.С.; Зайченко, А.Д.; Торпаков, А.С.; Липян, Е.В.; Жданов, А.А. (Вісник Українського матеріалознавчого товариства, 2013)
The influence of high voltage electric discharge (HED) on the peculiarities of grinding, shape and phase composition change of powder mixtures, based on iron and titanium of different mass composition, is studied. It is found out, that HED processing of Fe–Ti powders in all modes indepently from mass compositions leads to the increase in quantity of fine particles (sized less than 1μm) of spherical shape. The effectiveness of grinding depends on integral energy only in narrow range up to ~1 MJ. It is shown, that HED processing contributes to forming of carbides (TiC, Fe3C), hydrides (TiH) and intermetallics Fe2Ti.